Local folds and creases in the midst of the global map: reticense and resistance - Richard, Nelly; Universidad Arcis, Chile (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2006)
The article describes the new forms for resistance in the economic and semiotic grids of the capitalist continuum. Empire, with its globalized signs of cross-border nature, has replaced the old symbols of deeply rooted traditions and belonging. It is a ‘trans-semiotic’ grid of connectivity and ‘non-differentiation’, marked by the perpetual movement of meanings and the speed of exchanges. As a proposal, it moves forward in the concept of ‘hybridity’, through the problem of ‘cultural tradition’, which ends up bringing about ruptures between what is global and what is local through the transfer of meanings from one chain to another. In spite of those who insist that ‘local’ is not out of the global order, the “no place” opposes “all places” of the empire. This figure represents the liberating conditions of crowds, which is “to be against in all places”, a characteristic that is not local –as a place– but of production of locality, that is, non belonging and permanent ‘de-inscription’.